Storytelling as a motivating tool for elementary students to use their school library an experimental study - Castillo, Moira L. (2001)
This was an experimental study that sought to prove the claim that the storytelling motivates the students belonging to use their school library. In the study, the independent variable is the storytelling that was conducted by the researcher, while the two dependent variables are the number of students who entered the school library and the number of books that they borrowed.